Higher Educational Institutions of Kazakhstan in the Global Educational Space. (Journal of Educational Sciences, 2017)
Globalization processes affect the national borders and free trade of goods, services and workforce around the world, and educational services are not exception. This article studies the relevance and benefits for Kazakhstanihigher education institutions attracting foreign students as a factor of Kazakhstan’s participation in the international education market. An analysis of official statistics for the 15 year period doesn’t show a positive  trend in the increase of foreign student numbers in higher educational institutions of Kazakhstan, which, we believe, requires attention, particularly in the context of the internationalization of higher education in Kazakhstan. Describe the reasons for recruiting international students: soft power, the development of a multicultural society and economic benefits. Thedata of the survey of international students who chose Kazakhstan as the country of study. The authors identified limitations that affect the low popularity of the Kazakhstan education. The proposed development of an overall strategy of attracting foreign students in Kazakhstan’s higher education institutions.
Keywords: foreign students; mobility; internationalization of higher education